Depression as a moderator of STAIR Narrative Therapy for women with post-traumatic stress disorder related to childhood abuse. Issue 1 (1st January 2017) - Cloitre, Marylene; Garvert, Donn W.; Weiss, Brandon J.
ABSTRACT: Background : Depression among those who have experienced childhood abuse is associated with earlier onset, more persistent and severe symptoms, more frequent relapse, and poorer treatment outcomes across a variety of psychiatric disorders. In addition, individuals with a history of childhood abuse are more likely to develop post-traumatic stress disorder (PTSD) co-occurring with depression. Objective : This study evaluated whether severity of depression moderated the outcome in a PTSD treatment for childhood abuse survivors. Specifically, we assessed whether individuals with significant depression obtained better outcomes when provided with a two-module treatment which included a skills training component with behavioral activation interventions, Skills Training in Affective and Interpersonal Regulation (STAIR) followed by a trauma-focused component, Narrative Therapy, as compared to two control conditions where one component (STAIR or Narrative Therapy) was replaced with Supportive Counseling. Method : Participants were 104 women with PTSD related to childhood abuse. Participants were randomized into three conditions: (1) STAIR plus Narrative Therapy (SNT), (2) STAIR plus Supportive Counseling (SSC), and (3) Supportive Counseling plus Narrative Therapy (SCNT). Clinician-Administered PTSD Scale for DSM-IV (CAPS-IV) PTSD symptom severity was assessed at pre-treatment, post-treatment, and 3 and 6 month follow-up. Results : Participants with severe depression showed superior PTSD symptom reduction following SNT, while those in the other two conditions experienced a loss of improvement after treatment ended. A similar finding was obtained among those with moderate depression, while among those with low levels of depression, outcomes did not differ across the three treatment conditions. Conclusions : Childhood abuse survivors with severe depression obtained superior outcomes in a treatment that combined skills training with trauma-focused work. Skills packages which contain behavioral activation interventions in combination with trauma-focused work may be particularly beneficial for patients with childhood abuse and severe depression.